PELATIHAN TEKNOLOGI CERDAS UNTUK MEMULAI BISNIS START UP DAN MANAJEMEN KEUANGAN BISNIS PT. MELUKIS SENYUM INDAHMU - I Nyoman Switrayana; L. Jatmiko Jati; Wisnu Alfiansyah; Muhlisin Muhlisin; Mohammad Ziad Anwar; Rini Adriani Auliana (Jurnal Pengabdian kepada Masyarakat, 2024)
The younger generation is creative and ambitious, often channeling this energy into startups. Observations by the community service team at Bumigora University reveal that most students aspire to establish startups to fulfill their needs and gain entrepreneurial experience. However, they face challenges such as limited knowledge of effective business strategies and financial management. This community service activity aims to enhance students' understanding of building and managing startups using smart technologies, particularly Artificial Intelligence (AI). The seminar introduces AI as a tool for developing business strategies, optimizing operations, and automating financial management. The program employs the Asset-Based Community Development (ABCD) method, focusing on leveraging community assets to address their needs. Activities include lectures, interactive sessions, and practical demonstrations to integrate AI into entrepreneurship. Results show a significant improvement in students' knowledge and skills in applying AI for business purposes. The seminar effectively enhanced their understanding of strategies for building businesses, designing marketing plans, and managing finances. Post-test results from participants via Google Form confirm these outcomes. This activity empowers the younger generation to establish competitive, technology-driven businesses.